Penerapan Model Rapid Application Development pada Aplikasi Helpdesk Trouble Ticket PT. Satkomindo Mediyasa - Maulana Ardhiansyah (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2019)
PT. Satkomindo Mediyasa is a limited liability company engaged in providing satellite-based telecommunications infrastructure networks (Very Small Aperture Terminal / VSAT). In an effort to service customer VSAT network connections, PT. Satkomindo Mediyasa often gets various reports of complaints from its customers. However, the complaints report management process that has been running so far is still not effective, causing the handling of customer complaints to run slowly and require a long time. In formulating the solution to the problem, it is proposed a helpdesk trouble ticket information system to help PT. Satkomindo Mediyasa in managing complaints reports is faster and more effective. Information systems were developed using the PHP and MySQL programming languages. The system development model used is Rapid Application Development (RAD) by being modeled through Unified Modeling Language (UML) diagrams. The results of this study produce a trouble ticket helpdesk information system that helps PT. Satkomindo Mediyasa in managing customer complaints reports is faster and more effective.